2018
DOI: 10.1002/cptx.52
|View full text |Cite
|
Sign up to set email alerts
|

Generating Germ‐Free Drosophila to Study Gut‐Microbe Interactions: Protocol to Rear Drosophila Under Axenic Conditions

Abstract: As several diseases have been linked to dysbiosis of the human intestinal microflora, manipulation of the microbiota has emerged as an exciting new strategy for potentially treating and preventing diseases. However, the human microbiota consists of a plethora of different species, and distinguishing the impact of a specific bacterial species on human health is challenging. In tackling this challenge, the fruit fly Drosophila melanogaster, with its far simpler microbial composition, has emerged as a powerful mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…Previous investigations have revealed that insect gut microbiota can be transferred vertically via depositing gut bacteria on the egg surface (Behar et al, 2008). Embryo dechorionation is an important step as it has been confirmed that eggshell layer carries microbes from adults (Sabat et al, 2015; Kolye et al, 2016; Kietz et al, 2018). Recently, it has been verified that D .…”
Section: Discussionmentioning
confidence: 99%
“…Previous investigations have revealed that insect gut microbiota can be transferred vertically via depositing gut bacteria on the egg surface (Behar et al, 2008). Embryo dechorionation is an important step as it has been confirmed that eggshell layer carries microbes from adults (Sabat et al, 2015; Kolye et al, 2016; Kietz et al, 2018). Recently, it has been verified that D .…”
Section: Discussionmentioning
confidence: 99%
“…Gnotobiotic animals are organisms associated with only a defined and controlled set of microorganisms. In contrast to mice, gnotobiotic Drosophila are easy to generate and maintain [54]. One of the widely used protocols consists in dechorionation of embryos with bleach, sterilizing with ethanol, washing in sterile water and transferring to fly food supplemented with a cocktail of broad-range antibiotics to avoid environmental contamination.…”
Section: Introductionmentioning
confidence: 99%
“…Essential heat-sensitive compounds such as bioactive peptides or vitamins might be better preserved by HEEB treatment rather than autoclaving. Unlike Drosophila larvae that grow well under axenic conditions on several autoclaved diets ( Brummel et al 2004 , Ridley et al 2012 , Newell and Douglas 2014 , Koyle et al 2016 , Kim et al 2018 ), other insect species such as Musca domestica ( Schmidtmann and Martin 1992 , Watson et al 1993 ) and Musca autumnalis (Diptera: Muscidae) ( Hollis et al 1985 ) were found to be strongly dependent on the presence of microbes for their growth. Cohen (2015) suggested that larva-associated microbes synthesize essential nutrients (e.g., vitamins, amino acids, signaling molecules, and sterols) that may otherwise be lacking in insect diets.…”
Section: Protocol 1: Establishment Of Sterile Viable and Growing Blmentioning
confidence: 99%
“…Samples of the diet (poultry feed), frass collected by the developed device, and larval gut homogenate from the control group were analyzed for metabolites associated with insect and microbial digestion ( Cohen 2015 , Kim et al 2018 ). Similar to the method used for black soldier fly larvae by Bonelli et al (2019) the larval gut homogenate sample was prepared using dissecting scissors by removal of the chitin, fat body, and trachea surrounding the gut from three larvae.…”
Section: Protocol 2: Frass Collection To Study Black Soldier Fly Larvmentioning
confidence: 99%